Patient-related outcome measures and clinical evaluation of dental implant therapy in the elderly population – a cross-sectional study - Dragović, Svetlana; Lazić, Zoran; Dragović, Miroslav; Vukadinović, Miroslav; Miličić, Biljana; Špadijer Gostović, Aleksandra (Vojnosanitetski pregled, 2021)
Background/Aim. Oral health disorders are crucial regarding general health and quality of life of the elders. The aim of this cross-sectional study was to evaluate the long-term clinical and patient-centered outcomes of dental implants, placed in partially and fully edentulous people older than 65 years. Methods. A total of 38 participants with an overall number of 168 implants were selected and underwent clinical and radiological examination. The implant survival rate, implant failure rate and other complications were recorded and analyzed. All participants agreed to respond to the Oral Health Impact Profile-14 (OHIP-14) questionnaire and another questionnaires on the Visual Analog Scale (VAS) related to their experiences and satisfaction with the overall implant treatment. Univariate and multivariate regression models were used to verify the relation between the OHIP score and the VAS questionnaires’ items. Results. The implant survival rate was 94.3%. The number of implants without any complication was 73.2% (123), while biological and technical ones occurred in 17.3% (29) and 9.5% (16) implants, respectively. Regarding quality of life, significant difference was found only between those who wear fixed and removable restauration (p = 0.001). The multivariate regression model showed that the degree of satisfaction with shape and size of dentures was significantly associated with lower OHIP scores, indicating a better quality of life. Conclusion. According to the results obtained, it can be concluded that dental implant therapy in elderly people can be considered as predictable long-term treatment option regarding high implant survival rate, minimal complications and significantly better quality of life found in the group with fixed dentures.
Keywords: dental implants; aged; surveys and questionnaires; quality of life; patient satisfaction